Advances in home-based respiratory muscle training for improving physical function in older adults with long COVID - Guo, Xu; Li, Xuemei (Frontiers in Physiology, 2025)
Long COVID imposes a substantial burden on older adults, manifesting as respiratory muscle dysfunction that severely compromises physical function. This narrative review synthesizes current evidence on home-based respiratory muscle training (RMT)—a non-pharmacological intervention targeting this impairment in older patients with long COVID—while critically evaluating its physiological mechanisms, therapeutic efficacy, implementation feasibility, and persistent challenges. Respiratory muscle dysfunction, caused by multifaceted neurophysiological and structural impairments, is a core mechanism of exertional dyspnea and fatigue in older adults, further aggravated by age-related decline. RMT mitigates these effects through improvements in respiratory strength, endurance, ventilatory efficiency, metaboreflex and autonomic regulation, and psychological wellbeing. Home-based RMT demonstrates non-inferior efficacy to conventional programs while providing critical accessibility for mobility-limited older adults. Nevertheless, implementation barriers include challenges in individualizing geriatric-adapted exercise prescriptions, technological access limitations, variable adherence, insufficient clinician training in remote assessment, and regulatory/policy gaps in telerehabilitation frameworks. Despite these challenges, home-based RMT represents a promising strategy for managing debilitating respiratory sequelae in this vulnerable population. This review consolidates RMT’s physiological rationale and clinical evidence, underscores its integration potential within collaborative care models, and outlines key translational priorities—including hybrid delivery systems and refined geriatric-specific protocols—to accelerate clinical adoption.